Leading in the paradoxical world of crises: How leaders navigate through crises - Charlotte Förster; Caroline Paparella; Stephanie Duchek; Wolfgang H. Güttel (Schmalenbach Journal of Business Research (SBUR), 2022)
Living and operating in a global world, the risk for a global economic crisis has never been greater. As ongoing events, such as the COVID-19 pandemic, the recent war in Ukraine or the sharply increasing inflation have shown, organizations need to be highly resilient to persevere in a crisis-prone world. Even though we know that crises serve as a focal lens on leadership behavior and leaders play a crucial role in these scenarios, little is known as to how leaders handle an existence-threatening organizational crisis. Using an inductive analysis of 32 interviews on crisis leadership, we show that in the case of an acute crisis, leaders apply different paradoxical behaviors to cope effectively with the situation and navigate their organizations through these events. More specifically, our study contributes to existing literature by, first, showing that the distinctiveness of crises results from the fact that leaders are confronted with paradoxes that they can otherwise smoothly separate in terms of time or organization, second, revealing that the leader's paradoxical behaviors as a respond are derived from their mindset to consciously recognize the contradictory demands of the crisis, and third, from their action in terms of a compressed situational leadership. By identifying six pairs of paradoxical behaviors, we demonstrate how leaders effectively deal with the unsolvable contradictions that arise from the crisis, and thus contribute to the organizations' ability to cope with crises.
Keywords: H12; 650; Leaders' behavior; Leadership; Organizational crisis; Organizational; resilience; Paradoxes